Respuesta :
Answer:
29
Step-by-step explanation:
Let a12 be the mean of the first 12 numbers:
a12=(sumOf12Numbers)/12.
So, sumOf12Numbers=12×a12
We add a new number, x:
a13=(sumOf12Numbers+x)/13
13×a13=12×a12+x
x=13×a13-12×a12=13×5-12×3=65-36=29
The thirteenth number is 29
Answer: The thirteenth number is 29
Step-by-step explanation: We shall by looking at the available bits of information. We already have a mean of 12 positive numbers which is 3. The addition of the numbers divided by 12 would result in the mean. This we can express as follows;
Summation/12 = 3
That basically is the formula for calculating a set of data/numbers.
If we cross multiply, the expression becomes;
Summation = 3 x 12
Summation = 36.
That means if we add up all 12 positive numbers we would have 36. When another is added the mean becomes 5. That is,
(36 + a)/13 = 5
That means the summation is now 36 + a, and the observed data is now 13, while the mean is now 5. Therefore,
(36 + a)/13 = 5
We cross multiply and we have,
36 + a = 5 x 13
36 + a = 65
Subtract 36 from both sides of the equation
a = 29
Therefore the 13th number is 29.